Investigation on Natural Convective Heat Transfer of Outside Micro-slender Cylinders - Hou Yali; Wang Jianwen; Liu Zhigang (Zhileng xuebao)
The natural convection outside micro-slender cylinders placed vertically with outer diameters from 39.9μm to 350.1μm with air is experimentally investigated. The Joule heat method is employed to obtain the Nusselt numbers in the experiment. The results are compared with the values of classical correlation equations. The investigations show that all values of classical correlation equations are different from each other, and the differences will decrease with decrease of the diameter of micro-slender cylinder. The deviation between experimental results and values of classical correlation equations will increase with decrease of the diameter, which can reach 50％.The heat transfer coefficient of natural convection increases with the decrease of the diameter of the micro-slender cylinder. These phenomena may be due to the enhancement of the natural heat transfer caused by the thinner boundary layer which resulted from the edge effect when the diameter of the micro-slender cylinder becomes smaller.